Rancang Bangun Aplikasi Terapi Wicara Grow SCDC (Special Child Development Centre) Berbasis Android - Faizin Fifaridillah; Atiqah Meutia Hilda (Prosiding Seminar Nasional Teknoka, 2020)
The Grow SCDC (Special Child Development Center) is one of the therapy centers for children's health development, where the activities include several therapy facilities for the development of children with health problems. One of the distractions is language or speech. Speech therapy application is built based on android using the Extreme Programming method. The speech therapy application uses the text to speech method and the speech to text method. The text to speech method is done by saying the name of the card containing the picture and the name of the card. When a card is selected, the application will say the name of the card. The text to speech method is carried out in the guess card game feature. The card guessing game contains a list of cards that can be guessed using the voice button, when the voice button is pressed, the voice issued by the user will be recorded and then the voice recording will be converted into text. The text results will be matched with the name of the selected card, the text will be checked whether the answer is true or false. This speech therapy application is designed and made with several programming languages, namely Dart, PHP (Perl Hypertext Preprocessor), the Flutter framework and a supporting package namely the Cloud Speech API for implementing the text to speech and speech to text methods. Meanwhile, the database management system uses MySQL software. It can be concluded in this study features and functions in the application are in accordance with the wishes of the respondents because it has an average questionnaire value of 87%, with a statement that the speech therapy application is stable and smooth for respondents.